DETERMINANT OF EARLY MENARCHE AT MUARA MEGANG ELEMENTARY SCHOOL SOUTHERN SUMATRA - Kiki Yusika; Sri Rahayu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Backgrounds: High rate of early menarche is one of the problems that should be the focus of government attention because the health impact will be in the future. The purpose of this study was to determine the effect of diet, physical activity and exposure to mass media on early menarche at Students Elementary School Muara Megang Southern Sumatra 2017. Methods: This research used a quantitative study with cross sectional design. Purposive sampling technique was done in the fifth and sixth graders with total population of 69 people. After selecting those who experienced early menarche, thirty respondents were eligible in this study. Univariate, bivariate correlation test, and multivariate multiple linear regression were employed to analyze the data. Results: The correlation test resulted in the score of diet (p-value=0.001), physical activity (p- value=0.040<0.05) and exposure to mass media (p-value=0.454). It was concluded eating patterns and physical activity had significant correlation with early menarche among students. Meanwhile, the mass media exposure had no significant influence to incidence of early menarche. Multivariate test results were obtained from the results of multiple linear regression tests of eating patterns (0.011<0.05) affecting the incidence of early menarche while physical activity (0.463>0.05) and exposure to mass media (0.733>0.05) had no effect on the incidence of early menarche. Conclusions: This study recommends a need of coordination between health center and the health office to conduct counseling or form peer consultants involving young women to be more able to get to know themselves.